Effects of temperature, duration, and solution conditions on physicochemical properties, antioxidant activity, and volatile carbonyl compounds in glucosamine caramels - Chan, Ai Chee; Siti Umairah, Mokhtar; Hong, Pui Khoon (Malaysian Institute of Chemistry, 2026)
The non-enzymatic browning of glucosamine (GlcN) generates advanced glycation end-products (AGEs) and volatile carbonyl compounds (VCCs), which have both beneficial and detrimental health effects. This is the first systematic study investigating how high temperature and solution type affect the caramelisation of GlcN, which participates in both Maillard and caramelisation reactions. Caramels were produced by incubating GlcN (20% w/v) in water, phosphate, or acetate buffers at 80, 100, and 120 °C for one or two hours. Physicochemical properties, antioxidant activity, and VCCs profiles were evaluated. Browning progression, indicated by absorbance at 280, 320, and 420 nm, revealed concurrent formation of pre-melanoidins and melanoidins. Acetate-buffered caramels exhibited the darkest colour, highest pH, and significantly greater antioxidant activity (ABTS and DPPH, p<0.05). In contrast, water-based systems produced the highest levels of 5-hydroxymethylfurfural (5-HMF) at 120 °C for 2 h. Methylglyoxal and glyoxal were the most abundant in acetate-based samples at 100 °C for 1 h, while diacetyl concentrations were comparable across systems at 120 °C. The presence of reactive carbonyls and AGE precursors highlights both functional potential and safety considerations in GlcN-derived caramels. Overall, GlcN caramelisation offers a promising natural antioxidant but warrants attention to thermal and compositional control for safe application.